Emaus cum figuris 3: Grotowski – Rembrandt – Caravaggio - Kosiński, Dariusz (Relacyjność w kulturze i sztuce: Księga jubileuszowa Profesor Małgorzaty Leyko, 2025)
The article proposes a comparison between some famous iconographical repre-sentations of the Supper in Emaus (scene taken from the Gospel according to St. Luca) and the aesthetics of Jerzy Grotowski’s poor theatre, especially of his last theatre production, Apocalypsis cum figuris (1969). An investigation to discover some correspondences between the two is developed to suggest a deeper connec-tions between the liturgy established in Emaus and dramaturgical model of Gro-towski’s theatre.